1983
DOI: 10.1093/clinchem/29.2.375
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular alkaline phosphatase and an immunoglobulin G that inhibited alkaline phosphatase in a patient's serum.

Abstract: Macromolecular alkaline phosphatase (EC 3.1.3.1) was found in the serum of a patient suffering from myasthenia gravis (adult type II) complicated with thymoma, and was shown by immunoelectrophoresis to be bound to immunoglobulins A and G (IgG). Placental alkaline phosphatase, complexed with either the patient's serum or IgG purified from the patient's serum, remained at the origin on electrophoresis, with significant loss of activity. Intestinal alkaline phosphatase, complexed with either the patient's serum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Since introducing the PEG precipitation test we have investigated 57 patients for the presence of macroenzymes. Including the one case (case 1) of macroamylasaemia (macroAMY) and one of macro-LDH (case 9) encountered during the production of reference ranges as described, we have, at time of writing, identi¢ed 12 cases of macroenzymaemia (positives/total tested): ¢ve with macroAMY (5/21); three with macroAST (3/3); one macroLDH (1/3); one typical of type 1 macroCK 1,3 plus one typical of type 2 macroCK 11,12 (2/18); and one composed mainly of an electrophoretically slow-moving band consistent with macroALP 13,14 (1/5). No patients have, as yet, been identi¢ed as having macroGGT (0/6) or macroALT (0/1).…”
Section: Patientsmentioning
confidence: 99%
“…Since introducing the PEG precipitation test we have investigated 57 patients for the presence of macroenzymes. Including the one case (case 1) of macroamylasaemia (macroAMY) and one of macro-LDH (case 9) encountered during the production of reference ranges as described, we have, at time of writing, identi¢ed 12 cases of macroenzymaemia (positives/total tested): ¢ve with macroAMY (5/21); three with macroAST (3/3); one macroLDH (1/3); one typical of type 1 macroCK 1,3 plus one typical of type 2 macroCK 11,12 (2/18); and one composed mainly of an electrophoretically slow-moving band consistent with macroALP 13,14 (1/5). No patients have, as yet, been identi¢ed as having macroGGT (0/6) or macroALT (0/1).…”
Section: Patientsmentioning
confidence: 99%
“…is method will not detect complexes to immunoglobulins other than IgG so has limitations [10]. In a further case study, Nagakawa et al [13] reported an intestinal ALP-IgG complex in which the IgG had the ability to inhibit ALP in a patient's serum. e electrophoretic mobility of the unusual form of ALP found in this patient coincided with that of the intestinal enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In these reports, the following characteristics of macro ALPs were demonstrated: (1) most were bound to IgG; (2) isoenzymes in the complexes were all of the liver or bone type, except in one case; (3) most of the complexes showed a broad band at the intestinal ALP on electrophoresis except in one case; (4) macro ALP had a specific antigen-antibody complex; and (5) ALP-IgG complexes were prevalent in serum from patients with ulcerative colitis. In 1983, Nakagawa et al [193] reported that lipase-IgG complex was present in the serum of a patient with malignant non-Hodgkin's lymphoma. In 1990, Viallard et al [195] reported that enolase [EC 4.2.1.11]-IgG complex was present in the serum of a patient with squamous cell lung cancer.…”
Section: Othersmentioning
confidence: 99%